Loop electrosurgical excision procedure treats cervical intraepithelial neoplasia 2/3 among HIV− and HIV+ women in Kenya - Mehta, Naaman; Orang'o, Omenge; Itsura, Peter; Tonui, Philip; Bussmann, Hermann; Bogers, J. P.; Liu, Tao; Cu-Uvin, Susan (Journal of lower genital tract disease, 2020)
Objective - The aim of the study was to compare loop electrosurgical excision procedure (LEEP) as treatment for cervical intraepithelial neoplasia (CIN) 2/3 in HIV− versus HIV+ women. - Materials and Methods - Seventy-five HIV− and 75 HIV+ women at 6 months or more after LEEP for CIN 2/3 were enrolled between September 2013 and November 2014 in this prospective cohort study at the cervical cancer screening clinic in Eldoret, Kenya. Visual inspection with acetic acid (VIA), followed by cervical cytology with conventional cytology, was performed on all women. Women with positive VIA or abnormal cervical cytology underwent colposcopy/biopsy. Lesion progression, persistence, and regression were assessed to quantify the efficacy of LEEP. - Results - Post-loop electrosurgical excision procedure screening test showed both a negative VIA and normal cervical cytology in 64 (85%) of HIV− and 57 (77%) HIV+ women (risk difference = 8.3%, CI = −4.2% to 21%, p = .20). Eleven (15%) HIV− and 17 (23%) HIV+ (p = .20) women had positive VIA, abnormal cervical cytology, or both and were referred for colposcopy/biopsy. Twenty-one (8 HIV−, 13 HIV+) women were biopsied. Of the 8 HIV− women, 4 (50%) had CIN lesions that regressed, 3 (38.0%) persisted, and 1 (12%) progressed to invasive cancer after LEEP. Of the 13 HIV+ women, 6 (46%) had CIN lesions that regressed, 7 (54%) had CIN lesions that persisted, and no HIV+ women had CIN lesions that progressed after LEEP. There was no difference in estimated efficacies of LEEP for HIV− and HIV+ women (92.7% versus 89.4%, risk difference = 3.3%, CI = −4.8% to 15.3%, p = .85). - Conclusions - Loop electrosurgical excision procedure for CIN 2/3 is effective treatment for HIV− and HIV+ women in low-resource settings. Future efforts should improve follow-up after treatment.
Gesehen am 17.04.2020